Rancang Bangun Sistem Monitoring Cuaca Berbasis Google Spreadsheet Untuk Nelayan Di Wilayah Pesisir Pantai - M Mahrus Hidayat; Agus Dwi Santoso; Maulidiah Rahmawati (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Coastal areas are vital areas for fishing activities, and the weather in this area plays a very important role in the safety and efficiency of fishermen's operations. Fishermen on the coast often face the challenges of weather that is changeable and can be very extreme, including strong winds that can cause high waves and unsafe sea conditions. Therefore, the development of a Google spreadsheet-based weather monitoring system for fishermen in coastal areas is very relevant and strategic to support safer and more productive fishing activities. This research aims to make it easier for fishermen to monitor the weather in coastal areas in real time. Testing is carried out by running the system for observation for a predetermined time duration. This research uses an anemometer, DHT11 and raindrop sensors connected to a NodeMCU ESP32 microcontroller to send data to a Google spreadsheet, with readings of wind speed, temperature, air humidity and rain values. This research was carried out at the Nusantara Prigi fishing port, Trenggalek, challenging the work of anemometer sensors, DHT11 and raindrop sensors. Testing of tools and data obtained by comparing data on wind speed, temperature and air humidity using a digital anemometer and digital thermometer hygrometer humidity. The results of this research are that a Google spreadsheet-based weather monitoring design for fishermen in coastal areas can monitor wind speed, air humidity, temperature and detect rain online using a spreadsheet application and functions well with an average error accuracy of 3%.